2021
DOI: 10.1002/da.23223
|View full text |Cite
|
Sign up to set email alerts
|

Prior histories of posttraumatic stress disorder and major depression and their onset and course in the three months after a motor vehicle collision in the AURORA study

Abstract: Background: A better understanding of the extent to which prior occurrences of posttraumatic stress disorder (PTSD) and major depressive episode (MDE) predict psychopathological reactions to subsequent traumas might be useful in targeting posttraumatic preventive interventions. Methods: Data come from 1306 patients presenting to 29 U.S. emergency departments (EDs) after a motor vehicle collision (MVC) in the advancing understanding of recovery after trauma study. Patients completed self-reports in the ED and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This might be because patients who come to EDs after MVCs without serious injuries and/or who agree to be in studies like AURORA have high CA prevalence. Consistent with this possibility, a prior AURORA report noted that pre-MVC lifetime PTSD and MDE were substantially higher than in general population surveys (Joormann et al ., 2022 ). Although we have no way to investigate causes, it is noteworthy that prior research has shown that people who experience MVCs have high prevalence of substance problems (Bogstrand et al ., 2012 ) and that people who choose to go to EDs after traumas are more likely than those who do not to have preexisting mental health problems (Krieg et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This might be because patients who come to EDs after MVCs without serious injuries and/or who agree to be in studies like AURORA have high CA prevalence. Consistent with this possibility, a prior AURORA report noted that pre-MVC lifetime PTSD and MDE were substantially higher than in general population surveys (Joormann et al ., 2022 ). Although we have no way to investigate causes, it is noteworthy that prior research has shown that people who experience MVCs have high prevalence of substance problems (Bogstrand et al ., 2012 ) and that people who choose to go to EDs after traumas are more likely than those who do not to have preexisting mental health problems (Krieg et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, only the first three of these were used as controls in multivariable models, as the others might have been influenced by CAs and thus more likely to be mediators than confounders. A previous AURORA investigation found that three MVC characteristics predicted 3-month PTSD and/or major depressive episode (MDE), the two types of APNS considered here: any vehicle damage, concussion and severe pain reported in the ED (Joormann et al ., 2022 ). Vehicle damage was reported by the patient in the ED.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations